2014
DOI: 10.1155/2014/730678
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from Curcuma zedoaria Inhibit Proliferation of Human Breast Cancer Cell MDA‐MB‐231 In Vitro

Abstract: Objective. To evaluate the effect of petroleum ether extracts of Curcuma zedoaria on the proliferation of human triple negative breast cancer cell line MDA-MB-231. Methods. The reagents were isolated from Curcuma zedoaria by petroleum ether fraction. It was assayed by CCK8 for MDA-MB-231 cellular viability with various concentrations and days, cell cycle analyses, Western Blot analysis, and Realtime Reverse Transcriptase PCR analyses for chemokines molecules including E-cadherin, and E-selectin, and adhesion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…C. rhizoma is widely used in the therapy of UL but absolutely prohibited for the pregnant women in clinics (1517). It possesses anti-inflammatory and anti-tumor activities and responds to multiple regulation of signaling pathways for ECM deposition (18), cell cycle arrest (19), and UL process (20). Moreover, TCM has long established the concise and synergistic effects of C. rhizoma and S. rhizoma , and, as a consequence, a compound with both was developed for UL therapies (21).…”
Section: Introductionmentioning
confidence: 99%
“…C. rhizoma is widely used in the therapy of UL but absolutely prohibited for the pregnant women in clinics (1517). It possesses anti-inflammatory and anti-tumor activities and responds to multiple regulation of signaling pathways for ECM deposition (18), cell cycle arrest (19), and UL process (20). Moreover, TCM has long established the concise and synergistic effects of C. rhizoma and S. rhizoma , and, as a consequence, a compound with both was developed for UL therapies (21).…”
Section: Introductionmentioning
confidence: 99%
“…Bunge (Chinese name Huang Qi, HQ), and Shi (courier) herb Glycyrrhiza uralensis Fisch (Chinese name Gan Cao, GC). Each herb in the formula can inhibit cancer growth via cell cycle arrest, apoptosis induction, and immune regulation ( Fu et al, 2014a ; Gao et al, 2014 ; Wang et al, 2014 , 2015b ; Feng et al, 2017 ). In addition, each herb is a drug that is frequently prescribed to cancer patients according to statistical analyses of the medication rules of national TCM masters ( Song et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extract of Bai jie zi—sinapine exhibited growth-suppressive activity and reversed multidrug resistance in MCF/dox cancer cells [9]. Whereas E zhu extracts presented cytotoxic effect on BC cells and induced ROS formation and cell apoptosis [10,11]. The current study demonstrated that YHD exhibited antitumor activity against BC xenografts in nude mice.…”
Section: Introductionmentioning
confidence: 82%